Acute Ischemic Stroke in SARS-CoV, MERS-CoV, SARS-CoV-2: Neurorehabilitation Implications of Inflammation Induced Immunological Responses Affecting Vascular Systems - Karimi, Leila; Sales, Carmela; Crewther, Sheila Gillard; Wijeratne, Tissa (Frontiers in Neurology, 2020)
Coronaviruses (CoVs) belong to enveloped RNA viruses and have been shown to cause mild to severe respiratory infections in humans, with many more severe cases inducing neurological manifestations. The lethality of the Severe acute respiratory syndrome (SARS-CoV), Middle-East respiratory syndrome (MERS-CoV), and recently the Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has been documented; however, literature is scarce regarding the long term effects and the implications for neurorehabilitation. Neurological manifestations of SARS-CoV-2 and MERS-CoV have been linked to the SARS associated inflammatory cytokine storms and hypercoagulopathic states. This mini-review provides an overview of the commonalities among studies published on all three types of the coronavirus related to acute ischemic stroke (AIS), intending to further elucidate the physiological mechanisms underpinning CoVs related AIS that might enhance challenges for neurorehabilitation clinicians post COVID, carefully balancing the provision of services useful to the patient and the reduction of the risk of spreading the virus. In terms of increased incidence of AIS, it is likely that in depth knowledge of increased thrombotic risk in this population will become necessary and appropriate anticoagulation, other therapeutic interventions and neurorehabilitation interventions will become important in the management of stroke in COVID-19.